Triterpenoids from the Stem Bark of Aglaia cucullata (Meliaceae) and Their Cytotoxic Activity against A549 Lung Cancer Cell Line - Desi Harneti; Iqbal Wahyu Mustaqim; Darwati Darwati; Al Arofatus Naini; Purnama Purnama; Erina Hilmayanti; Tri Mayanti; Nurlelasari Nurlelasari; Shabarni Gaffar; Rani Maharani; Kindi Farabi; Sofa Fajriah; Mohamad Nurul Azmi; Yoshihito Shiono; Unang Supratman (Indonesian Journal of Chemistry, 2023)
The Aglaia species, which contains triterpenoids, is the most numerous in the Meliaceae family. The A. cucullata species, of which there are only a few known examples, has received scant research attention. This investigation aims to identify triterpenoids in an n-hexane preparation of A. cucullata stem bark and evaluate their effects against the A549 lung cancer cell line. Five dammarane-type triterpenoids were isolated from the A. cucullata trunk bark, which is (1) (20S)-20-hydroxydammar-24-en-3-one, (2) cabraleone, (3) cabralealactone, (4) eichlerianic acid, and (5) (+)-fouquierol. Their chemical structures were determined using infrared, high-resolution mass spectrometry, and nuclear magnetic resonance, as well as through data comparison of the reported compounds. Compound 1 was priorly separated from the Aglaia genus, compounds 2–4 were first isolated from the A. cucullata species, and compound 5 has been reportedly isolated from the Meliaceae family and the Aglaia genus. All substances were tested for their lethal potential against the A549 lung cancer cell type. A seco structure in the A ring of dammarane-type triterpenoid might play an important part in the lethal activity of component 4, which showed the greatest activity with an IC50 value of 32.17 µM against the A549 lung cancer cell line.